SUPERFICIAL CERVICAL PLEXUS BLOCK - Komang Mega Puspadisari (E-Jurnal Medika Udayana, 2014)
Superficial cervical plexus block is one of the regional anesthesia in  neck were limited to thesuperficial fascia. Anesthesia is used to relieve pain caused either during or after the surgery iscompleted. This technique can be done by landmark or with ultrasound guiding. The midpointof posterior border of the Sternocleidomastoid was identified and the prosedure done on thatplace or on the level of cartilage cricoid.